Bone Fragility in Turner Syndrome: Mechanisms and Prevention Strategies - Faienza, Maria Felicia; Ventura, Annamaria; Colucci, Silvia; Cavallo, Luciano; Grano, Maria; Brunetti, Giacomina (Frontiers in Endocrinology, 2016)
Bone fragility is recognized as one of major comorbidities in Turner Syndrome (TS). The mechanisms underlying bone impairment in affected patients are not clearly elucidated, but estrogen deficiency and X-chromosomal abnormalities represent important factors. Moreover, although many girls with TS undergo recombinant growth hormone (rGH) therapy to treat short stature, the efficacy of this treatment on BMD is controversial. The present review will focus on bone fragility in subjects with TS, providing an overview on the pathogenic mechanisms and some prevention strategies.